On Maximal Subsemigroups of Partial Baer-Levi Semigroups - Boorapa Singha; Jintana Sanwong (International Journal of Mathematics and Mathematical Sciences)
Suppose that X is an infinite set with |X|≥q≥ℵ0 and I(X) is the symmetric inverse semigroup defined on X. In 1984, Levi and Wood determined a class of maximal subsemigroups MA (using certain subsets A of X) of the Baer-Levi semigroup BL(q)={α∈I(X): dom α=X and |X∖Xα|=q}. Later, in 1995, Hotzel showed that there are many other classes of maximal subsemigroups of BL(q), but these are far more complicated to describe. It is known that BL(q) is a subsemigroup of the partial Baer-Levi semigroup PS(q)={α∈I(X):|X∖Xα|=q}. In this paper, we characterize all maximal subsemigroups of PS(q) when |X|>q, and we extend MA to obtain maximal subsemigroups of PS(q) when |X|=q.